The Influence of Organizational Communication, Organizational Culture, and Organizational Commitment on Employee Performance at PAM Tirta Mangkaluku Palopo - Ramadansyah, Agung; Fahrezy, Irgy Ahmad; Alfiati, Helmi; Muliadi, Muliadi; Erwina, Erwina (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study examines the influence of organizational communication, organizational culture, and organizational commitment on employee performance at PAM Tirta Mangkaluku, Palopo City. As a Regional-Owned Enterprise (BUMD) engaged in clean water supply, the organization balances business sustainability with social responsibility to provide affordable and safe water services. Effective communication, strong organizational culture, and high employee commitment are considered essential factors for achieving this mission. The research employed a quantitative approach using questionnaires, interviews, and observations. Data were analyzed through descriptive statistics and multiple linear regression, including F-tests and t-tests, to evaluate both simultaneous and partial effects. Results revealed that the independent variables significantly affect employee performance both collectively and individually. The regression equation showed positive coefficients for organizational communication (0.527), organizational culture (0.505), and organizational commitment (0.536), indicating that improvements in these factors directly enhance performance. The F-test confirmed simultaneous significance with an F-value of 84.519 3.354 and a significance level of 0.000. These findings are consistent with organizational communication theory (Goldhaber, 1993), Scheins organizational culture model (2010), and Meyer and Allens commitment framework (1997). The study suggests that strengthening communication systems, cultivating a positive culture, and fostering employee commitment are crucial strategies for enhancing performance and sustaining effective public service delivery.